Robustness analysis of steel structures with various lateral load resisting systems under the seismic progressive collapse. (January 2018) - Tavakoli, HamidReza; Afrapoli, Majid Moradi
Abstract: Robustness is called to non-sensitivity of a structure to local damage. In the literature of Civil Engineering, the sensitivity of structures to the local damage which can cause a progressive collapse is called Robustness Index. After 9/11, progressive collapse drew the attention of researchers and since that time, increasing the Robustness Index in a structure has been considered as one of the factors in strengthening the structure against progressive collapse. The aim of this study is assessing the Robustness Indices of steel structures having various lateral load resisting systems. So, 8-story, 4-story and 15-story structures with Moment Frames, Concentrically Braced Frames and Eccentrically Braced Frames were modeled and assessed under Robustness analysis. For a progressive collapse analysis, the Alternative Load Path method was used and after emerging local damage, the potential of progressive collapse was assessed using the Robustness Index. First, Robustness analysis was carried out on the basis of Robustness Index assessment using Stiffness and Base Shear methods. Subsequently, it continued by introducing a simple method based on Energy. The results show that despite their simplicity, the methods which are based on Stiffness and the Base Shear, have lots of disadvantages. But, the Energy method has better capabilities for understanding the behavior of structure under seismic loads in progressive collapse scenario. Furthermore, structures which have bracing had a better reaction in progressive collapse scenario. Highlights: To assess the effects of inducing local damage to various structures the plastic strain energy current. Comparing the behavior of structural systems under progressive collapse. Uncertainties in structures such as stress ratios, number of elements, number of stories, degrees of the fixed ends, etc. The Robustness Index declines with increasing PGAs, and the structures get near to Zipper collapse limits in higher PGAs.